2017
DOI: 10.32398/cjhp.v15i2.1900
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Opinions Regarding the Interface between Oral and Overall Health among California Physicians, Dentists, Pharmacists and Advanced Practice Registered Nurse Practitioners

Abstract: Background and Purpose: Oral health is often related to other medical conditions. This study investigated the knowledge and opinions of California physicians, dentists, pharmacists, and advanced practice registered nurses (APRNs) regarding the interface between oral and overall health and their suggestions for strengthening this interface. Methods: A survey packet was mailed to randomly-selected California healthcare providers in Winter 2015. Twenty five-point Likert-type questions were used to measure the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Cumulative data of our study results revealed that 66% of community pharmacists asserted, lack of a regular meeting with dental professionals as one of the barriers in providing oral health services. Furthermore, the lack of proper knowledge is the second most stated barrier 1‐3,6,7 . These barriers can be resolved by proper integration in the healthcare system.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Cumulative data of our study results revealed that 66% of community pharmacists asserted, lack of a regular meeting with dental professionals as one of the barriers in providing oral health services. Furthermore, the lack of proper knowledge is the second most stated barrier 1‐3,6,7 . These barriers can be resolved by proper integration in the healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, remarkable efforts are required to bridge oral and general healthcare. This can be achieved through increasing awareness and knowledge of the bidirectional relationship between oral health and general health among the healthcare professionals 2 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations